The Role of Social Media Exposure Frequency, Sustainability Valuation and Entrepreneurship Intention on Entrepreneurship Sustainability of Undergraduate Students - Setyoko, Paulus Israwan; Kurniasih, Denok (IJOSMAS, 2022)
This study aims to analyze the relationship between student assessments of sustainability, frequency of social media exposure, and student motivation for entrepreneurship to assessment of sustainability in entrepreneurship. This study uses a quantitative approach and the sample taken for this study amounted to a minimum of 299 undergraduate students. Questionnaires were created and distributed using Google Forms which were distributed online through social media. This study uses a five-scale Likert scale using a measurement of 'agree' or 'disagree' using a five-scale Likert scale. This research is a quantitative research using the SmartPLS 3.0 program. Structural equation modelling (SEM) is used to analyze the correlation or interrelationships between the variables being studied. The results showed that the assessment of sustainability, the frequency of exposure to social media, and the drive for entrepreneurship did have an effect on the assessment of student sustainability in entrepreneurship.